New Monoclonal Antibody to PCSK9 Markedly Lowers LDL-C in Patients on Atorvastatin - Buckley, Rita (MD Conference Express, 2012)
Proprotein convertase subtilisin/kexin type 9 serine protease (PCSK9) binds to low-density lipoprotein receptors (LDLRs) and plays a pivotal role in LDLR degradation [McKenney JM et al. J Am Coll Cardiol 2012]. This article discusses outcomes on the low-density lipoprotein cholesterol-lowering effects of SAR236553/REGN727 (SAR236553), a highly specific, fully human monoclonal antibody to PCSK9 [Efficacy and Safety Evaluation of SAR236553 (REGN727) In Patients With Primary Hypercholesterolemia and LDL-Cholesterol on Stable Atorvastatin Therapy; NCT01288443].